Thiosemicarbazones Can Act Synergistically with Anthracyclines to Downregulate CHEK1 Expression and Induce DNA Damage in Cell Lines Derived from Pediatric Solid Tumors - Paukovcekova, Silvia; Krchniakova, Maria; Chlapek, Petr; Neradil, Jakub; Skoda, Jan; Veselska, Renata (International journal of molecular sciences, 2022)
Anticancer therapy by anthracyclines often leads to the development of multidrug resistance (MDR), with subsequent treatment failure. Thiosemicarbazones have been previously suggested as suitable anthracycline partners due to their ability to overcome drug resistance through dual Pgp-dependent cytotoxicity-inducing effects. Here, we focused on combining anthracyclines (doxorubicin, daunorubicin, and mitoxantrone) and two thiosemicarbazones (DpC and Dp44mT) for treating cell types derived from the most frequent pediatric solid tumors. Our results showed synergistic effects for all combinations of treatments in all tested cell types. Nevertheless, further experiments revealed that this synergism was independent of Pgp expression but rather resulted from impaired DNA repair control leading to cell death via mitotic catastrophe. The downregulation of checkpoint kinase 1 (CHEK1) expression by thiosemicarbazones and the ability of both types of agents to induce double-strand breaks in DNA may explain the Pgp-independent synergism between anthracyclines and thiosemicarbazones. Moreover, the concomitant application of these agents was found to be the most efficient approach, achieving the strongest synergistic effect with lower concentrations of these drugs. Overall, our study identified a new mechanism that offers an avenue for combining thiosemicarbazones with anthracyclines to treat tumors regardless the Pgp status.
Keywords: Antibiotics, Antineoplastic; Topoisomerase II Inhibitors; DNA Damage; inhibitory topoisomerasy II; Checkpoint Kinase 1; Humans; antracykliny; P-glykoprotein; checkpoint kinasa 1; Anthracyclines; Thiosemicarbazones; lidé; Cell Line, Tumor; Doxorubicin; ATP Binding Cassette Transporter, Subfamily B, Member 1; Child; poškození DNA; doxorubicin; dítě; thiosemikarbazony; protinádorová antibiotika; nádorové buněčné linie